Young Women in Cities - Yumi Koh; Jing Li; Yifan Wu; Junjian Yi; Hanzhe Zhang (Institute of Labor Economics (IZA), 2023)
Young women outnumber young men in cities in many countries during periods of economic growth and urbanization. This gender imbalance among young urbanites is more pronounced in larger cities. We use the gradual rollout of special economic zones across China as a quasi-experiment to establish the causes of this gender imbalance. Our analysis suggests that a key contributor is gender-differential incentives to migrate due to rural women's higher likelihood of marrying and marrying up in cities when urbanization creates more economic opportunities and an abundance of high-income marriage-age men.
Keywords: O15; J12; 330; urbanization; migration; gender imbalance; labor market; marriage market